FEATURES OF THE LINGUISTIC CONTEXT IN THE FORMATION OF MEANING - Azimova , Sayyora Khusanboevna (Educational Research in Universal Sciences, 2023)
In this article, we will delve into the essential components of the linguistic context that contribute to the formation of meaning. By understanding the structure and form of language, we can comprehend how these features interact to give rise to nuanced interpretations. The examination of linguistic context is crucial for language learners, communicators, and researchers, as it sheds light on the intricacies of meaning creation.